COMMUNITY SERVICE INTERNALIZING JAVANESE CULTURAL VALUES IN SELF-CARE PARENTING TO SHAPE THE CHARACTER OF SCHOOL CHILDREN IN MEDAN TUNTUNGAN DISTRICT - Ira Maulani Lubis; Grace Mutiara; Cinta Uli Indriani Marpaung (Jurnal Masyarakat Indonesia (Jumas), 2025)
The challenges of parenting in the modern era require parents to implement a parenting style that pays attention to psychological aspects, such as self-care parenting. However, limited understanding often triggers parenting stress that adversely affects children's character. This community service activity aims to improve parents' understanding and practical skills regarding self-care parenting which is internalized with the noble values of Javanese culture. The program was carried out in Medan Tuntungan District by the academic team of STIKes Darmo Medan through pre-test and post-test quantitative evaluation methods. The results of the activity show that there is an increase in awareness and high enthusiasm from the community towards parenting based on local wisdom. In conclusion, structured education about the synergy of modern parenting and Javanese cultural values is effectively a strategy to create family resilience and form the character of school children who are disciplined, polite, and ethical.